International measures to protect women from gender-based violence and their impact on Iraqi legislation - Lecturer Dr. Hamida Ali Jaber (The college of law and political science journal, 2023)
Women are half of society, and they are the ones who give birth and raise the other half, as described by the wise men, Without women's participation, there will be no progress for any country. But women still suffering from gender-based discrimination and violence, which pose difficulties in the face of their real and effective participation in leading society towards living a good and dignified life. The documents confirm that gender-based violence is a widespread problem with regard to international human rights and public health, and that interventions to prevent and confront  gender-based violence in an appropriate, distinctive and effective manner are insufficient in most countries of the world. This type of violence increases and manifests itself in various forms, such as physical, sexual and psychological abuse, as well as honor killings, one of its major manifestations, forced and early marriages, trafficking in women, female genital mutilation, abuse and dropping out of education. The current century has witnessed the emergence of several legal international agreements that included a number of measures to protect women from gender violence. Several resolutions and declarations to reduce gender violence have emerged from the United Nations, and Iraq has put in place several legislation and strategies to protect women from gender violence. Despite all international efforts and its implications for the internal Iraqi legislation, the problem of gender-based violence still exists.